PERILAKU GRIT BERDASARKAN DEMOGRAFI KARYAWAN FOOD MANUFACTURING CONSUMER GOODS (FMCG) DI BANDAR LAMPUNG - Septania, Sovi (Universitas Islam Negeri Raden Intan Lampung, 2019)
Achieving long-term goals is the main focus of every company as a manifestationof a firm sustainability. Employees as the backbone of the company need positive behavior and a strong desire to achieve this long-term goal. This positive character with long-term assurance is called grit. The current problem is the high level of turnover of company employees which is one indicator of the lack of attachment of employees in achieving the company's long-term goals. Grit is predicted to be able to support the achievement of the company's long-term goals and empirically able to reduce turnover rates. The purpose of this study is to test empirically whether there are significant differences in grit behavior based on employee demographics in one of FMCG company in Bandar Lampung. This study uses a mixed method with a scale for quantitative data and open questions for qualitative data. The total subjects involved in this study were 115 employees. Data were analyzed using SPSS 24.0 program. The results showed that there were no significant differences in employee grit behavior in terms of age, sex, work period and education. The results of qualitative data analysis through data transformation found several possible main factors in working, such as good teamwork, assurance of occupational safety and health, adequate work facilities, a fair recognition system, a work environment that facilitates self-development, communication and good relations subordinate supervisors and consistent application of company regulations.